Evaluation The Sero-Prevalence of Cytomegalovirus Infection among Abortion Women in Baqubah city - Saja Hussain Kalaf; Zahraa Jaafar Jameel (ASJ - Academic Science Journal, 2023)
Cytomegalovirus (CMV) consider one of the opportunistic viruses, with a worldwidedistribution, that can infect humans at any stage of life. It is a major cause of prenatal andperinatal infections and may lead to important complications in pregnancy. This study aims toassess the serum anti-CMV antibody (IgG and IgM) levels in blood of women who sufferedabortion and correlation of aborted women with socio-demographic characteristics such as age,living, academic achievement, number of abortion, and fetus age This research was performedbetween November 2021 and January 2022 on 80 women suffering from abortion and 20healthy control women in Al-Batool Teaching Hospital in Baqubah city. ELISA test resultsshowed that the abortion women shown highest percentage of seropositive to CMV for IgG(96.3%) and (40%) IgM with a significant difference as compared to the control group (P